Computational models of discourse - Brady, Michael, 1945-; Berwick, Robert C.; Allen, James (MIT Press, 1983)
Annotation As the contributions to this book make clear, a fundamental change is taking place in the study of computational linguistics analogous to that which has taken place in the study of computer vision over the past few years and indicative of trends that are likely to affect future work in artificial intelligence generally.The first wave of efforts on machine translation and the formal mathematical study of parsing yielded little real insight into how natural language could be understood by computers or how computers could lead to an understanding of natural language. The current wave of research seeks both to include a wider and more realistic range of features found in human languages and to limit the dimensions of program goals. Some of the new programs embody for the first time constraints on human parsing which Chomsky has uncovered, for example. The isolation of constraints and the representations for their expression, rather than the design of mechanisms and ideas about process organization, is central to the work reported in this volume. And if present goals are somewhat less ambitious, they are also more realistic and more realizable.Contents:Computational Aspects of Discourse, Robert Berwick; Recognizing Intentions from Natural Language Utterances, James Allen; Cooperative Responses from a Portable Natural Language Data Base Query System, Jerrold Kaplan; Natural Language Generation as a Computational Problem: An Introduction, David McDonald; Focusing in the Comprehension of Definite Anaphor, Candace Sidner; So What Can We Talk About Now?Bonnie Webber.A Prefaceby David Israel relates these chapters to the general considerations of philosophers and psycholinguists.Michael Brady is Senior Research Scientist at the MIT Artificial Intelligence Laboratory. The book is included in the MIT Press Artificial Intelligence Series.
Keywords: Artificial intelligence.; Computational linguistics.; Speech processing systems.; elektronické knihy; electronic books